1991
DOI: 10.1136/gut.32.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing Helicobacter pylori ammonia production by urea infusion on plasma gastrin concentrations.

Abstract: It has been proposed that the hypergastrinaemia in subjects with Helicobacter pylon infection is caused by the action of the ammonia produced by the organism's urease activity on the antral G cells. To investigate this hypothesis we examined the effect on plasma gastrin of increasing the bacterium's ammonia production by infusing urea intragastrically to eight H pylori positive duodenal ulcer patients. After a 60 minute control intragastric infusion of dextrose solution at 2 ml/ minute, a similar infusion cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 10 publications
4
26
1
Order By: Relevance
“…(13) noted that healthy volunteers with H . pylori had increased basal and meal-stimulated gastrin concentrations compared with uninfected volunteers, yet there was no difference between the two groups with regard to (5)(6)(7). basal, maximal, or meal-stimulated acid outputs.…”
contrasting
confidence: 46%
“…(13) noted that healthy volunteers with H . pylori had increased basal and meal-stimulated gastrin concentrations compared with uninfected volunteers, yet there was no difference between the two groups with regard to (5)(6)(7). basal, maximal, or meal-stimulated acid outputs.…”
contrasting
confidence: 46%
“…H pylori has a remarkably high urease activity by which it hydrolyses urea to ammonia and carbon dioxide 17. As a result, patients with this infection have reduced concentrations of urea and increased concentrations of ammonia in their gastric juice 18. Several investigators have shown ammonia to be deleterious to the gastric mucosa, suggesting the importance of urease and ammonia in the pathophysiology of gastroduodenal diseases in H pylori infected patients 8…”
Section: Discussionmentioning
confidence: 99%
“…Levi et al postulated that ammonia produced by H. pylori might raise the pH of the antral mucosal surface, blocking the normal stimulation of somatostatin and the consequent inhibition of gastrin (17). However, neither increasing production of ammonia by H. pylori by intragastric infusion of urea (18), nor inhibiting ammonia production with acetohydroxamic acid (19) or 24 hours of triple antibacterial therapy (10) alters serum gastrin levels in H. pylori-infected individuals. The lack of an acute effect does not, however, exclude an effect from long-term production of ammonia by H. pylori on D cells and gastrin release.…”
Section: Hypergastrinaemiamentioning
confidence: 96%